Smoking Is Correlated With the Prognosis of Coronavirus Disease 2019 (COVID-19) Patients: An Observational Study - Peng, Fei; Lei, Si; Zhang, Quan; Zhong, Yanjun; Wu, Shangjie (Frontiers in Physiology, 2021)
Background Cigarette smoking has been proven to be a risk factor in the development of many diseases. However, it remains controversial with respect to the relationship of smoking with COVID-19. The purpose of this study was to explore the role of smoking in COVID-19. Methods A total of 622 patients with COVID-19 in China were enrolled in the study. Corresponding clinical and laboratory data were collected and analyzed. Meanwhile, Kaplan-Meier curve and Cox regression analysis were employed to analyze the association of smoking with survival in patients with COVID-19. Results Smoking was statistically significant comparing non-survivors and survivors of patients with COVID-19 (P=0.007). Males had higher proportion of smoking than females (91.9% vs. 8.1%, P <0.001). Compared with the non-smoker, there was significant statistical difference in the incidence of cerebrovascular disease in smoking patients with COVID-19 (9.7% vs. 3.4%, P=0.017). White blood cell count(6.3 vs. 5.4; P =0.037), hemoglobin level (139.0 vs. 127.0; P <0.001), and creatinine level (77.3 vs. 61.0; P <0.001) were significantly increased in COVID-19 patients who smoked. Moreover, smoking patients showed a worse survival compared with non-smoking patients (Log Rank P=0.045). After adjustment for age, gender and underlying diseases, patients with smoking still had higher risk of mortality than that of non-smoking patients. (hazard ratio [HR] 1.897, 95% confidence interval [CI] 1.058–3.402, P = 0.032) Conclusions Smoking was thought to be a risk factor in predicting the prognosis of COVID-19 and smoking patients might have a higher risk of mortality than that of the non-smoking patients.